Bacterial consortia constructed for the decomposition of Agave biomass - Maki, Miranda (Landes Bioscience, 2014)
Research has shown that a greater variety of enzymes, as well as variety of microorganisms producing enzymes, can have an overall synergistic effect on the decomposition of lignocellulosic biomass for the production of value-added bio-products. Here, 8 cellulase-degrading bacterial isolates were selected to develop co-, tri-, and tetra-cultures for the decomposition of lignocellulosic biomass. Glucose and xylose equivalents released from imitation biomass media containing 0.5% (w/v) beechwood xylan and 0.5% (w/v) Avicel was measured using di-nitrosalicylic acid for all consortia, along with cell growth and survival. Thereafter, 6 co- and 2 tri-cultures with greatest decomposition were examined for ability to degrade Agave americana fiber. Interestingly, when strains were paired up in co-culture, four pairs: G+5, G+A, C+A1, and G+A1 produced high reducing sugars in 24 h: 6 µM, 8 µM, 8 µM, and finally, 6 µM, respectively. From 4 co-cultures with highest reducing sugar equivalents, tri- and tetra-cultures were produced. The bacterial consortia which had the highest reducing sugars detected were 2 tri-cultures: G + A1 + A4 and G + A1 + 5, displaying levels as high as 9 µM and 5 µM in day 1, respectively. All co- and tri-cultures maintained high cell survival for 14 days with 0.5 g ground Agave. Upon evaluating Agave dry weight after treatment, it was evident that almost half the biomass could be decomposed in 14 days. Scanning electron microscopy of treated Agave supported decomposition when compared with the control. These bacterial consortia have potential for further study of value-added by-product production during metabolism of lignocellulosic biomasses.